2012
DOI: 10.1007/s00066-012-0080-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitizing effect of the novel Hsp90 inhibitor NVP-AUY922 in human tumour cell lines silenced for Hsp90α

Abstract: Pre-silencing of Hsp90α followed by Hsp90 inhibition did not enhance the radiosensitizing effect of NVP-AUY922 in both tested tumour cell lines. Future work will be done on stable transfection with shRNA against Hsp90α or simultaneous silencing of both Hsp90 isoforms, Hsp90α and Hsp90β, in order to optimize tumour cell killing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…These findings support the results of our γ-H2AX foci assay in which we observed increased production and persistence of radiation-induced DNA DSBs in cells treated with AUY922. Our observations that AUY922 causes a G2-M cell cycle arrest and downregulates components of the PI3K-AKT-mTOR pathway were consistent with other studies in non-prostate cancer cell lines [136,137]. With such compelling pre-clinical data we believe that HSP90 inhibition serves as a promising adjunct to RT and that combination treatment is warranted.…”
Section: Candidate Targeted Agents As Radiosensitizers In Prostatesupporting
confidence: 90%
“…These findings support the results of our γ-H2AX foci assay in which we observed increased production and persistence of radiation-induced DNA DSBs in cells treated with AUY922. Our observations that AUY922 causes a G2-M cell cycle arrest and downregulates components of the PI3K-AKT-mTOR pathway were consistent with other studies in non-prostate cancer cell lines [136,137]. With such compelling pre-clinical data we believe that HSP90 inhibition serves as a promising adjunct to RT and that combination treatment is warranted.…”
Section: Candidate Targeted Agents As Radiosensitizers In Prostatesupporting
confidence: 90%
“…26,39 Targeting Hsp90 with classic geldanamycin inhibitors and more recently with nongeldanamycin based inhibitors, such as AUY922, has demonstrated radiosensitization of cancer cell lines derived from several different histologies. [19][20][21][22][23][24][31][32][33][34][35] Hsp90 inhibition offers the theoretical possibility of potent radiosensitization through broad downregulation of multiple critical radioresistance pathways whose components are members of the Hsp90 clientele, such as signal transduction pathways (PI3K-Akt-mTOR) [12][13][14] and DNA damage response (DDR) pathways (ATR/Chk1). 31,38,40 This study suggests that AUY922 may indeed impart radiosensitization through multiple mechanisms: (1) reassortment of prostate cancer cells into G 2 -M, (2) downregulation of the PI3K-Akt-mTOR radioresistance pathway and (3) downregulation of the ATR-Chk1 DDR pathway.…”
Section: Auy922 Induced a G 2 -M Arrest In Prostate Cancer Cell Linesmentioning
confidence: 99%
“…Our observations that AUY922 causes a G 2 -M cell cycle arrest and downregulates components of the PI3K-AktmTOR pathway are consistent with other studies in non-prostate cancer cell lines. 32,33 A key factor for the clinical success of a radiosensitizer is the ability to selectively radiosensitize only tumor cells and not normal tissues. Previous in vitro preclinical studies have demonstrated that geldanamycin Hsp90 inhibitors do not radiosensitize non-cancerous cell lines.…”
Section: Auy922 Induced a G 2 -M Arrest In Prostate Cancer Cell Linesmentioning
confidence: 99%
“…However, neither pre-silencing of Hsp90 nor that of Hsp70 increases the radiosensitizing effect of the Hsp90 inhibitor NVP-AUY922 [14]. Alternatively, the induction of Hsp70 after pharmacological Hsp90 inhibition can be suppressed by concomitant PI3K inhibition with the pyridofuropyrimidine PI-103, a dual PI3K and mTOR inhibitor [15].…”
Section: Introductionmentioning
confidence: 99%